1996
DOI: 10.2527/1996.74102541x
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of intestinal metabolism and its impact on whole animal energetics.

Abstract: In digesting and absorbing dietary nutrients, the gastrointestinal tract consumes approximately 20% of all incoming energy. A substantial proportion of this consumption is due to the rapid turnover of cellular protein, which permits abrupt changes in gut size to occur, matching capacity with delivery. If it is size of the alimentary tract that constrains nutrient uptake, greater than 20% allocation of ME intake above maintenance to the gut would improve the growth rate of a young animal but the efficiency of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
132
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(138 citation statements)
references
References 0 publications
5
132
0
1
Order By: Relevance
“…Thus, abomasal infusion will probably reduce the AA available for milk production compared with intravenous infusions. It has been shown that there is a high rate of energy and protein turnover in the lumen wall and the PDV (Cant et al, 1996;Reynolds, 2002) and that there is a substantial metabolism of EAA during absorption by intestinal enterocytes (MacRae et al, 1997). Elevated luminal nutrient supply has shown to influence activity which promotes tissue growth (Cant et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, abomasal infusion will probably reduce the AA available for milk production compared with intravenous infusions. It has been shown that there is a high rate of energy and protein turnover in the lumen wall and the PDV (Cant et al, 1996;Reynolds, 2002) and that there is a substantial metabolism of EAA during absorption by intestinal enterocytes (MacRae et al, 1997). Elevated luminal nutrient supply has shown to influence activity which promotes tissue growth (Cant et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The portal-drained viscera (PDV; the intestine, pancreas, spleen and stomach) contributes approximately 35% of whole-body energy expenditure and protein synthesis, even though it represents ,6% of body weight (BW) (Cant et al, 1996;Burrin et al, 2000). Research over the past 15 years has established that the small intestine of pigs also plays an important role in the metabolism of both essential and nonessential amino acids (Stoll et al, 1998;Burrin et al, 2000;Wu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic activity of these tissues is considerable. The portal-drained viscera (PDV; including gastrointestinal tract, pancreas, spleen and associated adipose tissue) account for about only 3 to 6% of total body mass but their proportion on total energy consumption and wholebody protein turnover accounts for 20 to 35% (Cant et al, 1996;Reeds et al, 1999). The pivotal role of gastrointestinal tissues in both whole-body nutrient demand and systemic tissue supply was discussed in some recent papers (Schaeffer et al, 2003;Drackley et al, 2006).…”
mentioning
confidence: 99%